Effects of a Quillaja saponaria extract on weanling pig growth performance and immune function during an acute enteric disease challenge - J L Turner; J R Werner; C M Hill; K Skjolaas; S Hogge; K Herkleman; J Ernest Minton; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2000)
A total of 96 pigs (initially 19 lb and 17 d of age) was used in a 28 d growth trial to determine the effects of Quillaja saponaria (QS) extract on weanling pig growth performance and immune function in response to enteric disease challenge with Salmonella typhimurium (ST). Experimental treatments were arranged in a 2 × 4 factorial with main effects of disease challenge (control vs. ST challenge) and dietary addition of QS (0, 4, 8, or 16 oz/ton). The results suggest little beneficial effect of QS on growth performance or immune response in the presence or absence of ST challenge.; Swine Day, Manhattan, KS, November 16, 2000
Keywords: Swine day; 2000; Kansas Agricultural Experiment Station contribution; no. 01-138-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 858; Swine; Weanling pigs; Disease challenge; Salmonella; Quillaja